Deconstructing Esg Social Washing: Customary Land Annexation, FPIC Violations, and Sustainable Legal Certainty Frameworks - Chandra Erick Manaek Pandapotan Lumban Gaol (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The aggressive expansion of coal mining companies has exposed a critical regulatory gap at the highly contested intersection of customary agrarian rights and compliance with modern sustainable finance. This article examines the annexation of customary land without Free, Prior, and Informed Consent (FPIC), disguised as communal partnerships in ESG reports. The research aims to uncover the mechanisms of social laundering, the disregard of Constitutional Court Decision No. 35/PUU-X/2012, the exploitation of the lack of customary land certificates, and the formulation of a transformative legal accountability framework. Methodologically, this research employs a normative socio-legal approach, comparing factual and empirical precedents from the Sendawar District Court with the strict financial regulatory framework of POJK 51/POJK.03/2017, SEOJK 16, and the Global Reporting Initiative (GRI) standards. The research findings demonstrate a systemic failure of boards of directors to manage social risks in accordance with Good Corporate Governance (GCG) principles. This study formulates a framework for sustainable legal certainty that classifies ESG social laundering as capital market fraud and proposes the implementation of the P2SK Law, including administrative sanctions up to and including delisting of company shares.